Artificial intelligence and job performance of healthcare providers in China - Zheng, Qi; Jin, Yun; Xu, Xinying (Frontiers in Public Health, 2024)
Based on the data from standardised-trained residents in the First People’s Hospital of Yunnan Province in China, this study explores the influence of artificial intelligence (A.I.) applications on the job performance of healthcare providers, employing the ordinary least squares model. The study finds that the standardised-trained residents’ job performance positively correlates with A.I. applications. After handling the problems of endogenous and missing variables based on the propensity score matching method, as well as variable and alternation of regression model the results are still robust. In further discussion, patients’ support was found to mediate the relationship between A.I. and job performance, and under the same conditions, the job performance of female residents empowered by A.I. was found to be significantly better than that of their male counterparts. Contrarily, no heterogeneity was observed with regard to how A.I. impacts the job performance of medical practitioners and clinical medical technicians.